Logistyka w agrobiznesie - Parlińska, Maria (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
At present, after more than decade of functioning market economy in Poland and other Central European countries, and at the time of rising international competition and economic globalisation the enterprises seek new business strategies adapted to needs of changing economy. Logistic is more often understood as an effective forward and reverse flow and storage of goods, services, and related information between the point of origin and the point of destination. Despite the fact, that the term is not generally used, logistics tasks are executed under different concepts. In the USA, for instance, the following terms are used: * Physical Distribution Management, * Material Management, * Physical - Supply, * Total - Distribution etc. Within Polish enterprises, the growing interest of the data systems and of their implementation is observed. Some of them are as follows: * TPS - Transaction Processing Systems, * OAS - Office Automatization Systems, * MIS - Management Information Systems, * DSS - Decision Support Systems, * LIS - Logistics Information System. In the case of agribusiness, the full integration of farmer with institutional environment exercises, what should result in precise rules of co-operation including organised distribution of information between agribusiness chain. The logistic systems used both in production and distribution processes in agribusiness sector should guarantee the food deliveries due to the principle: "delivery in time", and as a consequence should assure its adequate quantity and quality at minimal transport costs.